THE EFFECT OF ACADEMIC PROCRASTINATION ON THE ACCOUNTING LEARNING ACHIEVEMENT USING SELF-EFFICACY AS MODERATING VARIABLE AT SMK YPKK 1 SLEMAN - Rahmah, Ismi Nur (Jurnal Pendidikan Akuntansi Indonesia, 2015)
This research has two objectives. First, it is aimed to determine the effect of Academic Procrastination on the Accounting Learning Achievement in Accounting Study Program at grade X of SMK YPKK 1 Sleman academic year of 2014/2015. Second, it is amied to determine the effect of Academic Procrastination on the Accounting Learning Achievement through Self-efficacy as moderating variable in Accounting Study Program at grade X of SMK YPKK 1 Sleman academic year of 2014/2015 The population in this study was the students in Study Program at grade X of SMK YPKK 1 Sleman consists of 54 students. Data collection in this research were Questionnaire and Documentation. The questionnaires consisted of academic procrastination and self-efficacy instruments while the documentation was used to obtain Accounting Learning Achievement data. Research results showed that: (1) There is a significant negative effect of Academic Procrastination on the Accounting Learning Achievement in Accounting Study Program at grade X of SMK YPKK 1 academic year of 2014/2015, with rx1y = 0.575; r2x1y = 0.331; t-count -5.068 > t-table and sig 0.000 < 0.05; (2) There is significant negative effect of Academic Procrastination on the Accounting Learning Achievement through Self-efficacy as moderating variable in Accounting Study Program at grade X of SMK YPKK 1 academic year of 2014/2015, with rx1y = 0.699; r2x1y = 0.489; t-count -2.030 > t-table and sig 0.048 < 0.050. Keywords: Accounting Learning Achievement, Academic Procrastination, Self-efficacy